Improving Student Learning Outcomes Using Inquiry Learning Models in Natural Science Subjects (AJER: Advanced Journal of Education and Religion, 2024)
This research is motivated by the low student learning outcomes in natural science subjects (IPA) in the matter of changes in the form of objects. This is characterized by low learning outcomes with an average score of only 60 while the minimum completeness criterion (KKM) that has been set and must be achieved is 75. This study also aims (1) to find out the application of the inquiry learning model to subjects Science in class V MI Mamba'ul Ulum. (2) to find out the increase in student learning outcomes through the inquiry learning model in science subjects in class V MI Mamba'ul Ulum, with a total of 12 students. The research method used in this research is collaborative classroom action research (PTK), namely in the research process the researcher works with the subject teacher. consisting of two cycles. Data collection is done through tests, interviews, and observation. The results showed that by applying the inquiry learning model it was proven to be able to improve the learning outcomes of fifth grade students in the natural sciences subject matter of changes in the shape of objects. The student learning outcomes experienced an increase in the cycle as follows, in the pre-cycle the percentage of students' classical completeness was only 8.33%, which was included in the very less category, with an average value of 56.16. At the stage of cycle I, the percentage of classical completeness obtained, namely 75%, was included in the fairly good category with an average score of 88.91. and at the stage of cycle II the percentage of classical completeness obtained was 100% and was included in the very good category, with an average score of 95.33. Based on the results of the study it can be concluded that learning using the inquiry learning model can improve student learning outcomes.